Occurrence and risk assessment of organotin compounds in the surface water of the upper Yangtze River Estuary - Dai, Qi; Chen, Ling; Li, Pan; Xia, Shengji; Wang, Yanyan; Huang, Qinghui (Frontiers in Environmental Science, 2022)
Organotin compounds (OTCs) are a category of persistent toxic substances with endocrine disrupting effects and may pose a risk to aquatic organisms and human health via water. This study collected 78 surface water samples from the drinking water source in the upper Yangtze River Estuary from July, 2018 to November, 2019. Out of the nine OTC targets, tributyltin (TBT), dimethyltin (DMT), trimethyltin (TMT), dibutyltin (DBT), and monobutyltin (MBT) were detected from more than 50% of water samples, with cumulative concentrations of OTCs ranging from 42.5 ± 54.0 to 421 ± 176 ng Sn L−1. The composition and concentrations of OTCs in the stormy months were different from those in other months. The concentrations of OTCs with the ebbing tide exceeded that in the flooding tide and increased when the flooding tide transitioned to the ebbing tide. A pulsed trend in concentrations of OTCs in river water was evident due to the impacts of rainfall runoff and the tidal currents. Identified sources of OTCs included ship antifouling paints, agricultural pesticides, and plastic waste. TBT in water sources poses a low risk to human health as well as a risk to the ecosystem, particularly during the stormy months.